Modified icing system containing mint leaf and citrus peel extracts: effects on quality changes and shelf life of Indian mackerel - Viji, P.; Binsi, P. K.; Visnuvinayagam, S.; Ravishankar, C. N.; Venkateshwarlu, G.; Gopal, T. K. S. (Indian Journal of Fisheries, 2016)
The efficacy of ice containing mint (Mentha arvensis) leaf extract (700 mg l-1) and citrus (Citrus aurantium) peel extract (1000 mg l-1) in retarding the biochemical, microbiological and sensory changes in whole Indian mackerel was assessed. Presence of extracts in ice significantly (p<0.05) reduced the generation of total volatile base nitrogen (TVB-N), trimethyl amine nitrogen (TMA-N) and free fatty acids (FFA) during storage. Moreover, a marked inhibition of lipid oxidation was also observed in samples stored in ice with extracts, as indicated by its lower peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) compared to that of control. Additionally, icing with extract substantially reduced the count of total viable bacteria, as compared with the samples stored under conventional icing system. According to sensory evaluation, shelf life of Indian mackerel was determined to be 13 days for fishes stored under conventional icing system, 15 days for fishes stored in ice containing citrus peel extract and 17 days for the fishes kept in ice containing mint extract.